2015
DOI: 10.5539/res.v7n5p137
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Anticipation Capacity Development Programme at Interpersonal Interaction

Abstract: The paper presents the experimental findings proving the need for the development of anticipatory competence of future non-science specialists as a component of their professional competence. The objective of the research is to improve the level of anticipatory skills of university students at verbal and cogitative and communicative levels via a developmental training programme. Anticipatory skills in a speech activity are considered as a factor of adequacy of communicative situations and effectiveness of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, in addition to these factors, individual psychological characteristics of the individual also influence the anticipation consistency, both in general and in speech activity (Appelbaum L. G., et al, 2014). For example, for the development of certain style and individual psychological features, the anticipation mechanisms can be the basis, and the set of specific personality traits is able to determine the style of anticipation activity (Solobutina, 2015). It should be noted that in some types of dysontogeny during infancy, infants have slowing down or the partial stop of probabilistic forecasting and anticipation development.…”
Section: Resultsmentioning
confidence: 99%
“…However, in addition to these factors, individual psychological characteristics of the individual also influence the anticipation consistency, both in general and in speech activity (Appelbaum L. G., et al, 2014). For example, for the development of certain style and individual psychological features, the anticipation mechanisms can be the basis, and the set of specific personality traits is able to determine the style of anticipation activity (Solobutina, 2015). It should be noted that in some types of dysontogeny during infancy, infants have slowing down or the partial stop of probabilistic forecasting and anticipation development.…”
Section: Resultsmentioning
confidence: 99%
“…1 Based on the results of numerous studies, it can be argued that anticipation abilities as a whole are involved in the processes of personality adaptation to changing environmental conditions. 2,3 Clinical, psychopathological, and experimental psychological studies have confirmed the role of violations of anticipation mechanisms in the etiology and pathogenesis of neurotic, psychosomatic disorders, and maladaptation of patients with personality disorders. 4,5 It was revealed that the violation of the processes of anticipation, in turn, leads to a mismatch of the adaptation system, and, as a consequence, to maladaptive behavior.…”
Section: Introductionmentioning
confidence: 96%